Effect of environmental stress factors on the expression of virulence genes and pathogenicity of lethal Bacillus cereus of bovine origin - Meng, Qinglei; Song, Lili; Chi, Shanshan; Wang, Haifeng; Li, Jie; Chen, Yunjiao; Liu, Zhilin; Zhang, Xin; Jia, Zelin; Cui, Jiayu; Wang, Xueli (Frontiers in Microbiology, 2025)
ObjectiveBacillus cereus (B. cereus) can be used as a probiotic or produce a variety of toxins that are pathogenic to humans and animals. Environmental stressors can affect the growth process of B. cereus and the expression of its virulence genes. Due to the limitations of methods such as pharmacological disinfection methods (there are limits to the use of antibiotics) and chemical disinfection methods (chemical methods may produce residues), attempts can be made to remove and reduce B. cereus infections through environmental stress factors.MethodsIn this study, the expression of four virulence genes (nheA, hblD, cytK, and entFM) of bovine-origin lethal B. cereus was investigated by qPCR under the effect of different environmental stressors. The extent of pathological damage to various organs of mice by B. cereus was observed by pathological sections.ResultsThe results showed that high temperature could inhibit the expression of B. cereus virulence genes. Expression of B. cereus virulence genes was affected under the influence of pH. Different salt concentrations could make the B. cereus virulence genes show low expression. Under a single environmental stressors, nheA, hblD, cytK, and entFM had the lowest expression at 40°C, pH 8.0, and were lowly expressed at all salt concentrations except the control group. The action of multiple environmental stressors affect the expression of virulence genes. Under multiple environmental stressors, nheA, hblD and cytK were least expressed at a temperature of 40°C, pH 6.0, and salt concentration of 3.0%, and entFM was least expressed at a temperature of 20°C, pH 8.0, and salt concentration of 1.5%. Animal pathogenicity tests have shown that environmental stressors affect the virulence of B. cereus.ConclusionThe level of virulence gene expression in B. cereus can be reduced by environmental stress factors, thus further reducing the risk of B. cereus to human health. This study provides some reference for the prevention and control of B. cereus disease.